Die Allzuständigkeit amerikanischer Gerichte : Berarbeitete Fassung Eines Vortrages Gehalten VOR Der Juristischen Gesellschaft Zu Berlin Am 22. Januar 2003. - Schütze, Rolf A. (De Gruyter, 2003)
The author deals with the questions of the international jurisdiction of US courts and reasons for the jurisdiction regulations unknown to German law.
Keywords: Jurisdiction -- United States.; Jurisdiction (International law); United States -- International status.; Antitrust law -- European Union countries.; Antitrust law (International law); Conflict of laws -- Antitrust law.; Procedure (Law); International law.; Jurisdiction.; United States.; Electronic books.